Best practices among 3rd Party Logistics (3PL) firms in Malaysia towards logistics performance - Mohamad Makmor, Mohamad Fared; Saludin, Mohamad Nasir; Saad, Mazni (HRMARS Management Academic Research Society, 2019)
Studies on best practices among the 3rd Party Logistics (3PL) firms towards logistics performance has been conducted broadly nowadays due to the growing rivalry and the needs for survival in the business especially for small players. Discovering the best practices structure as well as endorsing its significance on firms’ overall performance has been validated by solid evidence of research literature and reports. Owners and managers are looking for any practical methods to reduce firm’s operational costs and increase efficiency. The Logistics Performance Index (LPI) released by the International Trade and Transport Department of World Bank, which examines logistics performance in 160 countries, ranks Malaysia at the 41 position as in the 2018 report, showing a declining trend from rank 25 and 32 in the 2014 and 2016 reports, respectively. The declining trend give negative signal that the Malaysian logistics performance is getting worst. The purpose of this paper is to study the breadth of best practices as found in the literature, with emphasizing on effort to build a theoretical framework that further discover the adoption of best practices towards logistics performance by 3PL firms in Malaysia. This paper discuss two independent theoretical areas i.e. best practices and logistics performance in relation to the Malaysian’s logistics business operations. Exploring this theoretical areas suggest a research gap in which best practices is abstracted as a method that can be used to provide confirmatory test of its theoretical support to a body of knowledge in the ground of logistics studies.